2021
DOI: 10.3389/fmars.2021.680482
|View full text |Cite
|
Sign up to set email alerts
|

Combining Imaging Flow Cytometry and Molecular Biological Methods to Reveal Presence of Potentially Toxic Algae at the Ural River in Kazakhstan

Abstract: Algal blooms occur in freshwater bodies throughout the world, often leading to fish kills. Cases of these kills along the Ural River were reported in 2018–2019, involving significant amount of sturgeon in fish farming areas. In this study, the analysis of algal samples from the delta of the Ural River up to 100 km inland was carried out from August to December 2019 using imaging flow cytometry (IFC), molecular biological, and microscopic techniques. We identified the filamentous cyanobacteria Cuspidothrix issa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 121 publications
(130 reference statements)
1
10
0
Order By: Relevance
“…The use of complementary biology methods to validate and/or augment sequencing data was common practice in the reviewed MinION applications. Complementary methods included quantitative PCR (qPCR) [27,38,50,54,58,63,65,66,68,69,71,74], culturing [27,43,47,50,52,54,63,66,68,71,72,76], flow cytometry [54,65], and fluorescence in situ hybridization (FISH) microscopy [51]. Across a range of case studies, we reported significant correlations between MinION sequencing, qPCR, and culturing derived indications of faecal pollution in water [50,63,66,71].…”
Section: Complementary Biology Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…The use of complementary biology methods to validate and/or augment sequencing data was common practice in the reviewed MinION applications. Complementary methods included quantitative PCR (qPCR) [27,38,50,54,58,63,65,66,68,69,71,74], culturing [27,43,47,50,52,54,63,66,68,71,72,76], flow cytometry [54,65], and fluorescence in situ hybridization (FISH) microscopy [51]. Across a range of case studies, we reported significant correlations between MinION sequencing, qPCR, and culturing derived indications of faecal pollution in water [50,63,66,71].…”
Section: Complementary Biology Methodsmentioning
confidence: 93%
“…Amplification of specific genes or genome regions of interest, targeted with appropriate primers, additionally assures that the full capacity of the MinION is devoted to sequencing these genes or regions. Several studies used full-length 16S rRNA gene amplicon sequencing to characterize communities of bacteria and archaea [27,29,38,48,50,54,56,63,65,66,68,71], mostly with ONT's 16S barcoding kit. Long-range PCR amplicons spanning 3 kb of the rDNA cassette were used for the detection of algal bloom organisms [74].…”
Section: Amplification Of Genes Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the recent development of next-generation sequencing (NGS) technologies led to their availability for field analysis and offered an enormous perspective for HAB monitoring (Jung et al, 2018; Hatfield et al, 2020). Ocean color satellite images is another key to studying the temperature trends and response of marine phytoplankton to climate variability and change (Groom et al, 2019), plankton distribution in ocean, and detecting and predicting HABs (Stumpf et al, 2008; Walsh et al, 2011; Zhong et al, 2019; Tang and Liu, 2020; Mirasbekov et al, 2021; Iwataki et al, 2022). Given the substantial climate-driven shifts in coastal ecological systems, accelerated interdisciplinary efforts are required to understand how climate change will influence the HABs.…”
Section: Introductionmentioning
confidence: 99%